A Comparative Assessment of the Land Reform Programme in South Africa and Namibia - Vermeulen, Sanet Elenor (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Political Science))--University of Stellenbosch, 2009.